Aspirin inhibits cancer stem cells properties and growth of glioblastoma multiforme through Rb1 pathway modulation. Issue 9 (30th January 2019) - Pozzoli, Giacomo; Marei, Hany E.; Althani, Asma; Boninsegna, Alma; Casalbore, Patrizia; Marlier, Lionel N. J. L.; Lanzilli, Giulia; Zonfrillo, Manuela; Petrucci, Giovanna; Rocca, Bianca; Navarra, Pierluigi; Sgambato, Alessandro; et al.
Abstract: Several clinical studies indicated that the daily use of aspirin or acetylsalicylic acid reduces the cancer risk via cyclooxygenases (Cox‐1 and Cox‐2) inhibition. In addition, aspirin‐induced Cox‐dependent and ‐independent antitumor effects have also been described. Here we report, for the first time, that aspirin treatment of human glioblastoma cancer (GBM) stem cells, a small population responsible for tumor progression and recurrence, is associated with reduced cell proliferation and motility. Aspirin did not interfere with cell viability but induced cell‐cycle arrest. Exogenous prostaglandin E2 significantly increased cell proliferation but did not abrogate the aspirin‐mediated growth inhibition, suggesting a Cox‐independent mechanism. These effects appear to be mediated by the increase of p21 waf1 and p27 Kip1, associated with a reduction of Cyclin D1 and Rb1 protein phosphorylation, and involve the downregulation of key molecules responsible for tumor development, that is, Notch1, Sox2, Stat3, and Survivin. Our results support a possible role of aspirin as adjunctive therapy in the clinical management of GBM patients. Abstract : Aspirin strongly inhibits glioblastoma cancer stem cells proliferation and invasiveness by modulation of retinoblastoma (Rb1) pathway and key molecules responsible for cancer development, that is, Notch1, Sox2, Stat3, and Survivin.